ANALYSIS OF LEGAL PROTECTION FOR CONSUMER LOSSES DUE TO BUSINESS PERFORMER'S BREACH OF CONCERT ORGANIZER - Natalia, Fenny; Soemartono, Gatot P. (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
Currently, the music industry has become one of the most popular forms of entertainment among various segments of society. In this context, music concerts have become a significant source of revenue for promoters. However, it is not uncommon for promoters to neglect their responsibilities as business operators, resulting in losses for consumers who have purchased concert tickets. This research aims to examine the legal protection available to consumers who suffer losses due to the breach of contract by concert organizers. The research method used is a normative legal approach, analyzing legal issues through relevant legislation. The legal materials for this research are derived from primary and secondary legal sources, including legislation and related research findings on the subject matter. The research results indicate that consumer protection in Indonesia remains a serious concern, as business operators frequently fail to fulfill their obligations and violate consumer protection laws, leading to consumer losses. This study concludes the protection available to consumers seeking legal remedies for their losses, including claims for compensation in accordance with Law Number 8 of 1999 Concerning Consumer Protection.